Unveiling the Hidden Patterns: A Dermoscopic Analysis of Vitiligo Lesions at a Tertiary Care Center in Surakarta, Indonesia - Sesia Pradestine; Muhammad Eko Irawanto; Osdatilla Esa Putri; Trya Oktaviani; Benedicta Lauda Anandita (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Vitiligo, a common depigmenting disorder, presents with a variety of clinical manifestations. Dermoscopy, a non-invasive skin imaging technique, has emerged as a valuable tool for evaluating pigmentary disorders. This study aimed to analyze the dermoscopic patterns of vitiligo lesions in a cohort of patients at a tertiary care center in Surakarta, Indonesia, and to correlate these patterns with disease stability. Methods: This cross-sectional study included 20 adult patients diagnosed with vitiligo at the Dermatology and Venereology Outpatient Clinic of Dr. Moewardi Regional General Hospital Surakarta in July 2023. A dermoscopic examination was performed on all patients using a polarized light dermoscope. Dermoscopic features were analyzed and categorized based on the BPLeFoSK criteria (Border, Pigment Network, Lesions, Follicular, Koebner). Disease stability was assessed based on clinical and dermoscopic findings. Results: The majority of patients were female (75%) and between 21-40 years old (65%). All patients exhibited the characteristic "white glow" under dermoscopy. Other common findings included reduced or absent pigment network (40% each), perifollicular hyperpigmentation (30%), and perilesional hyperpigment (30%). Satellite lesions and micro-Koebner phenomenon, indicative of disease activity, were observed in 10% of patients each. Based on these findings, 80% of patients were classified as having stable vitiligo, while 20% had unstable vitiligo. Conclusion: Dermoscopy revealed a spectrum of patterns in vitiligo lesions, with the "white glow" being a universal finding. The majority of patients in this cohort had stable vitiligo. Dermoscopy can aid in assessing disease activity and guiding treatment decisions in vitiligo patients.